Natural history of widespread high grade prostatic intraepithelial neoplasia and atypical small acinar proliferation: should we rebiopsy them all?. (4th March 2021) - Oderda, Marco; Rosazza, Matteo; Agnello, Marco; Barale, Maurizio; Calleris, Giorgio; Daniele, Lorenzo; Delsedime, Luisa; Falcone, Marco; Faletti, Riccardo; Filippini, Claudia; Giordano, Andrea; Marquis, Alessandro; et al.
Abstract: Objective: To evaluate the premalignant potential of high-grade prostatic intraepithelial neoplasia (HGPIN) and atypical small acinar proliferation (ASAP). Methods: Patients diagnosed with monofocal HGPIN (mHGPIN), widespread HGPIN (≥4 cores, wHGPIN) and/or ASAP who underwent at least one rebiopsy during their follow-up, were enrolled. All enrollment biopsies underwent central pathologic revision. Risks for PCa were estimated using Fine and Gray method for competing risk. Results: Pathologic revision changed the original diagnosis in 32.3% of cases. Among 336 cases enrolled, PCa was diagnosed in 164 (48.8%), and more specifically in 20 (30.3%) mHGPIN, 10 (34.5%) wHGPIN, 101 (54.0%) ASAP, and 33 (61.1%) HGPIN + ASAP (mean follow-up 124 months). Most PCa were Gleason score 6(3 + 3) (51.0%) and 7(3 + 4) (34.3%). On multivariate analysis, HGPIN + ASAP (HR 2.76, p  < 0.001) and ASAP alone (HR 2.41, p  < 0.001) were the only lesions significantly associated with PCa development. Of all cancers detected, 64.3% were at first rebiopsy. A rebiopsy performed within 3 months after ASAP diagnosis had a 45% chance of finding PCa. At Kaplan–Meier survival curves, median PCa-free survival was 48.1 months for HGPIN + ASAP and 64.9 months for ASAP ( p 0.0005 at Log-rank test). At 1 year, 70% of HGPIN + ASAP, 73% of ASAP, 89% of wHGPIN, and 84% of mHGPIN were PCa-free. Conclusion: The diagnosis of ASAP and HGPIN strongly relies on the expertise of dedicated uro-pathologists. Finding of ASAP is a strong risk factor for a subsequent PCa diagnosis, advising a rebiopsy, possibly within 3 months. m/wHGPIN should not be routinely rebiopsied.